RESOLUSI KONFLIK SOSIO-EKOLOGI PADA TRADISI BALON UDARA - Priyaji Agung Pambudi; Savina Nurma Fardiani (Pangadereng : Jurnal Hasil Penelitian Ilmu Sosial dan Humaniora, 2022)
The hot air ballooning tradition as a local wisdom continues to raise pros-cons. It flights have a negative impact on humans and environment. Research is needed to conflict resolution, this research with a qualitative approach through physical, social observation, literature review, and in-depth interviews. This tradition in Ponorogo Regency has shifted because it was found a practice outside the Idul Fitri. It is exacerbated by the number of cases in economic losses, damage to settlements, public infrastructure, electricity services disruption, internet, forest fires, and fatalities. The results found that the negative impact of the tradition is more (18 points) than the positive impact (5 points) and has the potential to serious environmental damage. It is proposed that 7 points of conflict resolution need support from academia, business, government, community, and media (ABGCM) for the transformation into a better pattern for the preservation, safety, and the socio-system and the ecosystem harmonious.